Study on the Efficiency and Effectiveness in the Food Processing Industry: A Study on Efficiency and Effectiveness in the Food Processing Industry in India (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Introduction Small and medium-sized businesses in India are essential to the country's progress. Thesebusinesses are a reliable source of income for the government.Aim of the study the main aim of the study is Study on The Efficiency and Effectiveness in The FoodProcessing IndustryMaterial and method Two hundred business units in the food processing industry in Rajasthan wereselected at random for this study's sample.Conclusion This research makes use of secondary data on the food processing sector in India, drawnfrom the ASI time-series data on manufacturing throughout the 35-year period of 1973-2008.